Projected Seismic Activity at the Tiger Stripe Fractures on Enceladus, Saturn, From an Analog Study of Tidally Modulated Icequakes Within the Ross Ice Shelf, Antarctica. Issue 6 (7th June 2021) - Olsen, Kira G.; Hurford, Terry A.; Schmerr, Nicholas C.; Huang, Mong‐Han; Brunt, Kelly M.; Zipparo, Sophia; Cole, Hank M.; Aster, Richard C.
Abstract: Dissipation of tidal energy is expected to generate seismicity on icy‐ocean worlds; however, the distribution and timing of this seismic activity throughout an orbital cycle is not known. We used new observations from an icy‐ocean‐world analog environment on Earth to examine the relationship between tidally driven tensile stress and seismic activity within an ice shell. We investigated a pair of rifts within Antarctica's Ross Ice Shelf which are tidally stressed in a manner analogous to the orbital cycle of tidal stress experienced by Enceladus' Tiger Stripe Fractures. We found that seismic activity at the Antarctic rifts is sensitive to both the amplitude and the rate of tensile stress across the rifts. We combined these findings with calculated stress values along Enceladus' Tiger Stripe Fractures to predict seismic‐activity levels expected along the ice‐shell fractures. We predict a peak in seismicity along the four Tiger Stripe Fractures when Enceladus is 90°–120° past pericenter in its orbit around Saturn, at which point tensile stresses would reach ∼2/3 of their maximum value. We also used the magnitude distribution of icequakes along Antarctic rifts to investigate implications for the likely size of stick‐slip rupture patches along icy faults on Enceladus. Our findings predict that the Tiger Stripe Fractures should produce sustained, low‐magnitude seismic events that involve rupture along discrete portions of each fracture's total length. We predict that seismicity would fall to 50% of peak levels when stresses across the Tiger Stripe Fractures are dominantly compressional. Plain Language Summary: Saturn's moon Enceladus is covered in ice which contains many long fractures or rifts, including four fractures called the Tiger Stripes. As Enceladus orbits Saturn, tidal forces cause the Tiger Stripe Fractures to erupt tall geysers of water vapor. This suggests that there is liquid water somewhere beneath Enceladus' icy surface and that there must be motion along the fractures. We expect that this motion should generate icequakes, similar to earthquakes on Earth. In this study, we built a model to predict where and when icequakes occur along the Tiger Stripe Fractures, using what we know about ice in Antarctica. We use a large floating expanse of solid ice, the Ross Ice Shelf, which contains fractures that are similar to the Tiger Stripe Fractures. We investigate Antarctic icequakes and find that the majority of icequakes occur during falling tide, when the rifts are being stretched open. We predict that the majority of icequakes along the Tiger Stripe Fractures occur around 100° into Enceladus' orbit and that these icequakes are very small, but numerous. Our results are valuable to future landed missions to Enceladus or another icy‐ocean world, where icequakes will help us understand what lies beneath the ice. Key Points: We predict significant seismicity along all four Tiger Stripe Fractures on Enceladus, with peak seismic activity ∼100° past pericenter We find that rift seismicity is correlated with both applied tensile stress and tensile‐stress (stretching) rate Gutenberg–Richter b ‐value estimates for icequakes at studied rifts are ≥1.2, suggesting that b ‐values >1 are appropriate for icy shells